2022
DOI: 10.1177/08901171211059806
|View full text |Cite
|
Sign up to set email alerts
|

How Socioeconomic Status and Acculturation Relate to Dietary Behaviors Within Latino Populations

Abstract: Purpose Despite having lower socioeconomic status, Latinos in the US experience fewer adverse health outcomes than non-Latinos. However, they are disproportionately affected by diet-related diseases. Among other racial/ethnic groups, high acculturation and low socioeconomic status are associated with worse dietary intake, yet, few studies have investigated these relationships among Latinos. Design 2013–2014 NHANES analyzed to examine pathways through which acculturation, income, nativity, and food security are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Many previous studies reported that greater acculturation, measured by years in the United States, immigrant generation, or language preference, was related to poorer cardiovascular health 35,37,38 and poorer diet quality in US Hispanic and Latino populations. 30,33,34 No previous studies directly examined the association between dietary acculturation and incident CVD event risk in a US Hispanic and Latino population. Notably, age- and sex-adjusted prevalence of CVD is higher in HCHS/SOL compared with Hispanic/Latino countries of origin (Global Burden of Disease estimates/HCHS/SOL: Mexico, 5%/5.9%; Cuba, 6%/6.7%; Puerto Rico, 6.1%/10.1%; Dominican Republic, 6.6%/9%), 39 suggesting potential adverse effects of acculturation on cardiovascular health in US Hispanic/Latino immigrants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many previous studies reported that greater acculturation, measured by years in the United States, immigrant generation, or language preference, was related to poorer cardiovascular health 35,37,38 and poorer diet quality in US Hispanic and Latino populations. 30,33,34 No previous studies directly examined the association between dietary acculturation and incident CVD event risk in a US Hispanic and Latino population. Notably, age- and sex-adjusted prevalence of CVD is higher in HCHS/SOL compared with Hispanic/Latino countries of origin (Global Burden of Disease estimates/HCHS/SOL: Mexico, 5%/5.9%; Cuba, 6%/6.7%; Puerto Rico, 6.1%/10.1%; Dominican Republic, 6.6%/9%), 39 suggesting potential adverse effects of acculturation on cardiovascular health in US Hispanic/Latino immigrants.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary acculturation is a complex multidimensional process in which migrants often maintain their original cultural foodways while adopting dietary habits of the country in which they reside. 30 Traditional Hispanic and Latino diets are typically high in fiber, vegetables, and fruits and low in added sugars and processed food 31 ; in contrast, typical US diets are low in fruits and vegetables and high in fat, sodium, and sugar. 32 In HCHS/ SOL, participants with lower dietary acculturation had higher intakes of fruit, beans, whole grains, vegetables, and fish, and participants with greater dietary acculturation tended to consume more alcohol, refined grains, and sugar-sweetened beverages.…”
Section: Discussionmentioning
confidence: 99%
“…The cross-sectional study design limits inference about the direction of causality between PA and risk of MetS. We assessed acculturation by proxies, which are commonly used in research (Alegria et al, 2022; Le et al, 2019). However, proxy alone omits individual differences that cannot account for every domain of acculturation.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about male Latino college students and eating behaviors theorized to be causal factors for higher weight, despite elevated rates of higher body mass index (BMI) among Latinx undergraduates (37%; McEligot et al, 2021) and the prevalence of diet- or obesity-related diseases among Latino men in the United States (e.g., Alegria et al, 2022; Valdez et al, 2017). Schembre et al (2009) discussed theories about weight-related eating and overeating as a response to emotional or external stimuli or the outcome of food restriction and developed the Weight-Related Eating Questionnaire (WREQ) to measure routine restraint, compensatory restraint, susceptibility to external cues, and emotional eating.…”
mentioning
confidence: 99%
“…Research about acculturation, eating, and related body-image variables is mixed. Some studies have uncovered positive relationships between acculturation and unhealthy eating and body image in Latinx college students or adults (Bolstad & Bungum, 2013; López & Yamashita, 2017; Poloskov & Tracey, 2013), and some have not (e.g., Alegria et al, 2022; Warren & Rios, 2013). Only one study investigated enculturation in Latino college students and found no relationship with body image (Warren & Rios, 2013).…”
mentioning
confidence: 99%